Benzo-α-pyrene induced oxidative stress in Caenorhabditis elegans and the potential involvements of microRNA. (November 2015) - Wu, Hongmei; Huang, Chenping; Taki, Faten A.; Zhang, Yanqiong; Dobbins, Dorothy L.; Li, Lin; Yan, Hongtao; Pan, Xiaoping
Graphical abstract: Highlights: BaP exposure resulted in altered expressions of SKN-1 and GCS-1 in C. elegans . BaP exposure altered the expressions of microRNA in C. elegans . The response of GCS-1 to BaP might be independent of the regulation of SKN-1. The microRNAs might be involved in the regulations of SKN-1 and GCS-1 expression. Abstract: In the present study oxidative stress induced by Benzo-α-pyrene (BaP) exposure and the potential involvements of microRNA were investigated. The Caenorhabditis elegans ( C. elegans ) was applied as model organism. The C. elegans at L1-stage were randomly divided into 4 groups and exposed to 0, 0.2, 2.0, and 20 μM BaP for 30 h. Expressions of SKiNhead-1 (SKN-1), gamma-glutamine cysteine synthase heavy chain (GCS-1), and their potential regulatory factors in insulin/IGF-1/FOXO signaling pathway and the p38 MAPK pathway were analyzed. The expressions of potentially involved microRNAs were investigated as well. Results demonstrated that expressions of SKN-1 and GCS-1 were altered significantly following BaP exposure ( P < 0.05). Meanwhile, expressions of multiple related factors were changed after BaP treatments. The altered factors include AKT-1, DAF-16, glutathione synthetase (GSS-1), glutathione S-transferase-24 (GST-24), mitogen-activated protein kinase kinase-4 (MKK-4), multidrug resistance-associated protein-1 (MRP-1), and pyruvate dehydrogenase kinase-2 (PDHK-2) ( P < 0.05). In addition, results showed that exposure to BaP led to altered expressions of microRNA. Out of the 28 tested microRNAs, expressions of miR-1, miR-355, miR-50, miR-51, miR-58, miR-796, miR-797, and miR-84 were modified. Findings of the present study include that BaP exposure caused oxidative stress in C. elegans . The expressional response of GCS-1 to BaP exposure might be independent of the regulation of SKN-1 in C. elegans . The microRNAs might be involved in the regulations of SKN-1 and GCS-1 expression following BaP exposure in C. elegans .